2020
DOI: 10.1021/acsomega.0c04329
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reductive Alkylation of Amines in Batch and Microflow Conditions Using a Silicon-Wafer-Based Palladium Nanocatalyst

Abstract: We describe the development of the catalytic reductive alkylation of amines with aldehydes under the atmospheric pressure of H 2 using a brush-like silicon-nanostructure-supported palladium nanoparticle composite (SiNS–Pd) as a silicon-wafer-based reusable heterogeneous catalyst. The present reaction of primary and secondary amines with various aliphatic and aromatic aldehydes in the presence of the catalyst (0.02–0.05 mol % Pd) gave the corresponding secondary and tertiary amines includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Subsequently, different solvents were tested to improve the efficiency of resolution and the ratio of EtOH over water showed the significant effects in resolving efficiency and the optimal solvent was 95% EtOH, affording the (S)-1-D-tartaric acid in 36.7% yield with 99.06% chiral purity after two times of recrystallizations (entry 5). The direction of the specific rotation of freebase from this salt (α = À33.8[c = 1.08, MeOH]) was the same as that reported in the literature [7] (α = À30.5[c = 1.01, MeOH]), so the absolution configuration of (S)-1 was confirmed.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Subsequently, different solvents were tested to improve the efficiency of resolution and the ratio of EtOH over water showed the significant effects in resolving efficiency and the optimal solvent was 95% EtOH, affording the (S)-1-D-tartaric acid in 36.7% yield with 99.06% chiral purity after two times of recrystallizations (entry 5). The direction of the specific rotation of freebase from this salt (α = À33.8[c = 1.08, MeOH]) was the same as that reported in the literature [7] (α = À30.5[c = 1.01, MeOH]), so the absolution configuration of (S)-1 was confirmed.…”
Section: Resultssupporting
confidence: 82%
“…( S )‐2‐(3,5‐dimethylphenyl)pyrrolidine(( S )‐ 1 ) was a key chiral fragment in the synthesis of aticaprant, and the methods to synthesize ( S )‐ 1 mainly involved the asymmetric reduction of imine 4 under the catalysis of the chiral small molecule [5] or chiral metal [6]. Besides, it was also reported that ( S )‐ 1 could be obtained through the asymmetric induced synthesis, which was carried out with ( R )‐tert‐butylsulfonamide as chiral auxiliary and the starting materials were derived from Weinreb amide and Grignard reagent [7]. However, these methods suffered some deficiencies such as the requirement for costly catalysts, extreme reaction conditions (−78°C), and low reaction yield.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared with other catalyst ( Table 1 , entry 10), it is found that the initial reactant can be converted into the target product only under relatively harsh conditions (60 °C, 18 h, 160 mg catalyst). 64 In summary, the prepared catalyst enables the reaction of aniline and benzaldehyde to generate the target product under very mild conditions.…”
Section: Results and Analysismentioning
confidence: 97%
“… a Reaction conditions: 25 °C, atmospheric pressure, 5 mg catalyst, 0.5 mmol benzaldehyde, 1 mmol aniline, 3 mL solvent, H 2 balloon, reaction time: 1 h. b 1 mmol benzaldehyde. c 1 mmol aniline, 1.2 mmol benzaldehyde, 2 mL 2-propanol, 160 mg SiNS–Pd catalyst, 1.0 MPa H 2 , 60 °C, reaction time: 18 h. 64 …”
Section: Results and Analysismentioning
confidence: 99%
“…The intimate and direct contact of the binary reagents leads to enhanced mass transfer and facilitating reactions (Figure 9a). Yamada and coworkers [90] developed a brush-like silicon-nanostructure-supported palladium nanoparticle composite (SiNSÀ Pd, length ca. 500 nm, width ca.…”
Section: Silica Nanoarrays Prepared Via Chemical Etchingmentioning
confidence: 99%